The two-dimensional argument against materialism and its semantic premise (Diametros, 2011)
David Chalmers argues that zombies are possible because they are ideally conceivable and that therefore consciousness does not supervene on the physical. In this paper I discuss the most influential criticism of the conceivability-possibility principle in the current literature. According to that criticism, the conceivability-possibility principle is unjustified because it depends on a certain unjustified assumption concerning the semantic conditions under which necessary statements can be true a posteriori, namely that a posteriority is due to contingency at the reference-fixing level, so that a necessary statement can be true a posteriori only if at least one of the concepts flanking the identity sign refers contingently.